Pandemic Influenza A (H1N1) 2009 outbreak investigation in Nepal - Mahato, R K; Bhandari, G P; Shrestha, J M; Basnet, P (Journal of Nepal Health Research Council, 2011)
Background: The World Health Organization, on 24 April 2009, announced a Public Health emergency of international concern caused by a new influenza virus Pandemic Influenza A 2009. The objective of this study was to analyze the basic epidemiology and distribution of Pandemic Influenza A 2009 in order to understand the course of Pandemic Influenza A 2009 in Nepal. Methods: The analyses were based upon all confirmed and probable cases that consulted Avian Influenza Control Project and National Public Health Laboratory during 29 April 2009 to 21 September 2010. Results: Out of total 739 suspected samples collected, Pandemic Influenza A 2009 was detected in 210 cases in different districts of Nepal. The majority of cases were from the urban settlement of Kathmandu valley, Chitwan and Kaski and among age group 11-30 years. The clinical attack rate for Influenza like illness (ILI) was 28.48%. There was no significant difference between the clinical presentation of ILI and confirmed cases of Pandemic Influenza A 2009. Conclusions: This study presented the investigation of outbreak that helped to inform the course of epidemic in affected population and therefore urge for public health interventions. Key words: influenza, outbreak, pandemic